Room Temperature Ferromagnetism in InTe Layered Semiconductor Crystals Intercalated by Cobalt - V.B. Boledzyuk; Z.R. Kudrynskyi; Z.D. Kovalyuk; A.D. Shevchenko (Журнал нано- та електронної фізики)
The magnetic properties of CoxInTe layered crystals electrochemically intercalated with cobalt in constant gradient magnetic field and the morphology of the van der Waals surfaces of layers of these crystals were studied. It was established that impurity clusters consisting of cobalt nanoparticles are formed in the intercalates under investigation on the van der Waals planes in the interlayer space. It was revealed that at room temperature the investigated CoxInTe intercalates exhibit magnetic properties characteristic for magnetically hard ferromagnetic materials.